Gender Differences of Sustainable Consumer Behavior in Technology Adoption: Evidence From Indonesia - Ardiwansyah Nanggong; Rahmatia Rahmatia (Journal of International Conference Proceedings (JICP), 2018)
Eco-friendly behavior in the technology adoption is often motivated by psychographic dimensions. Moreover, sustainable consumer behavior depends on socio-demographic differences such as gender. This study focuses on investigating gender differences in the relationship between environmental concerns and perceived benefits of sustainable consumer behavior in the adoption of e-ticketing (paperless) technology. The research was conducted on e-ticketing users in Indonesia by collecting data through an online questionnaire. 188 respondents participated in this study. Finding of this study, the impact of perceived benefit is greater for male than for female and environmental concern is higher for female than for male in pro-environmental behavior when adopting the technology. Keywords: Gender, Perceived Benefit, Environmental Concern, Sustainable Consumer Behavior, Technology Adoption.